X‐ray fluorescence at nanoscale resolution for multicomponent layered structures: a solar cell case study. (2nd December 2016) - West, Bradley M.; Stuckelberger, Michael; Jeffries, April; Gangam, Srikanth; Lai, Barry; Stripe, Benjamin; Maser, Jörg; Rose, Volker; Vogt, Stefan; Bertoni, Mariana I.
Abstract : The study of multilayer stacks ( e.g. thin‐film solar cells) by X‐ray fluorescence requires a thorough account of the depth‐dependent attenuation of incident and excident X‐ray beam intensity, as well as spatial thickness variations to achieve an accurate interpretation of the data. A procedure is presented that allows for the assessment of stoichiometric composition variations in high spatial resolution imaging by correcting for multiple effects. Abstract : The study of a multilayered and multicomponent system by spatially resolved X‐ray fluorescence microscopy poses unique challenges in achieving accurate quantification of elemental distributions. This is particularly true for the quantification of materials with high X‐ray attenuation coefficients, depth‐dependent composition variations and thickness variations. A widely applicable procedure for use after spectrum fitting and quantification is described. This procedure corrects the elemental distribution from the measured fluorescence signal, taking into account attenuation of the incident beam and generated fluorescence from multiple layers, and accounts for sample thickness variations. Deriving from Beer–Lambert's law, formulae are presented in a general integral form and numerically applicable framework. The procedure is applied using experimental data from a solar cell with a Cu(In, Ga)Se2 absorber layer, measured at two separate synchrotron beamlines with varied measurement geometries. This example shows the importance of these corrections in real material systems, which can change the interpretation of the measured distributions dramatically.